Anatomical and Physical Study of the Wood of Apeiba tibourbou and Its Behavior During Air Drying - Leif Armando Portal-Cahuana; Willian Hancco-Ccahuantico; Jorge Cardozo-Soarez; Mauro Vela Da-Fonseca (Forest Science and Technology)
Natural wood drying is a key process in the timber industry, especially in tropical regions where climatic variations affect its efficiency. Apeiba tibourbou, commonly known as monkey comb, is a species from the Peruvian Amazon that presents favorable anatomical and physical characteristics for applications in lightweight products, although its behavior during air drying has been poorly studied. This study aimed to anatomically characterize the wood of A. tibourbou, evaluate its physical properties, and analyze its behavior during air drying in three stacking types (Horizontal, Sawhorse, and Triangular). The anatomical results showed an abundant presence of parenchyma in wide bands and small, sparse vessels, which are related to the low basic density of the wood (0.30 g/cm³), moderate shrinkage, and adequate dimensional stability. The Horizontal stacking method was the most efficient, reaching equilibrium moisture content in 140 days, while the Sawhorse and Triangular methods were slower and exhibited defects such as cracks and warping. These findings indicate that A. tibourbou has great potential for commercial applications in decorative and lightweight products, highlighting the importance of optimizing the air-drying process to improve its use in the timber industry.